2017
DOI: 10.1080/00918369.2017.1395259
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Examination of Identity Integration in Gay, Lesbian, and Bisexual People of Faith

Abstract: Much of the religious/spiritual development of gays, lesbians, and bisexuals (GLBs) has focused on experiences of conflict and distress, providing little insight into how these identities can be integrated. The present study explored the religious and spiritual lives of GLBs with a specific focus on the integration of these identities. We conducted a retrospective secondary data analysis of 750 GLB individuals from the Northern California Health Study to quantitatively assess sexual orientation and religion/sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
4
26
0
1
Order By: Relevance
“…Regarding our exploratory analyses, significant differences were found based on gender and sexual orientation regarding conflict between religious and LGB identities, with men reporting higher levels of conflict than women, and gay men reporting higher levels of conflict than bisexual/pansexual individuals, but not lesbian women. Our findings seem to mirror previous research by Rodriguez et al (2019), who showed that gay and bisexual males accounted significantly more to those who reported to struggle with their identity when compared with other sexual orientations and genders. Taken together, these findings suggest that males, and more specifically gay and bisexual males, may be affected disproportionality by conflict between religiosity/spirituality and their identities.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding our exploratory analyses, significant differences were found based on gender and sexual orientation regarding conflict between religious and LGB identities, with men reporting higher levels of conflict than women, and gay men reporting higher levels of conflict than bisexual/pansexual individuals, but not lesbian women. Our findings seem to mirror previous research by Rodriguez et al (2019), who showed that gay and bisexual males accounted significantly more to those who reported to struggle with their identity when compared with other sexual orientations and genders. Taken together, these findings suggest that males, and more specifically gay and bisexual males, may be affected disproportionality by conflict between religiosity/spirituality and their identities.…”
Section: Discussionsupporting
confidence: 89%
“…The relationship between conflict and well-being (or its absence) is another common experience reported by LGB people in qualitative and quantitative studies. Some people describe the way it has affected their well-being (Coyle & Rafalin, 2000) and/or their quality of life and mental health, including experiences of loneliness, depression, anxiety, and suicidal ideation (Beagan & Hattie, 2015; Dehlin et al, 2015; Lefevor et al, 2018; Rodriguez et al, 2019; Schuck & Liddle, 2001; Subhi & Geelan, 2012; Zeidner & Zevulun, 2018). Some participants also reported the experience of negative feelings and emotional scars, even after the conflict has been solved (Subhi & Geelan, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Brewster, Velez, Foster, Esposito, and Robinson (2016) reported that the benefits of positive religious coping actually weakened the negative impact of internalized heterosexism for sexual minority participants in terms of psychological distress and well-being. On a larger quantitative scale, Rodriguez, Etengoff, and Vaughan (2019) studied the relation between religious and sexual identity integration and well-being outcomes among 750 gay, lesbian and bisexual participants from largely Judeo-Christian backgrounds. Finding that religiously integrated participants scored the highest on measures of positive affect and a sense of a benevolent world as compared to those struggling with their religious and sexual identities, those that identified as secular and those with a low gay salience score (Rodriguez et al, 2019).…”
Section: Spiritual and Religious Resiliencementioning
confidence: 99%
“…On a larger quantitative scale, Rodriguez, Etengoff, and Vaughan (2019) studied the relation between religious and sexual identity integration and well-being outcomes among 750 gay, lesbian and bisexual participants from largely Judeo-Christian backgrounds. Finding that religiously integrated participants scored the highest on measures of positive affect and a sense of a benevolent world as compared to those struggling with their religious and sexual identities, those that identified as secular and those with a low gay salience score (Rodriguez et al, 2019).…”
Section: Spiritual and Religious Resiliencementioning
confidence: 99%